The potential of agroforestry and small fields to enhance ground-dwelling spiders - Manon Edo; Felix Herzog; Gerardo Moreno; Rodrigo Olave; Alice Ripamonti; Verena Rösch; Will Simonson; Lorenzo Gabriele Tramacere; Olivier Villepoux; Martin H. Entling (Agroforestry Systems, 2025)
Agroforestry systems integrate open and woody elements within agricultural landscapes, creating structurally complex ecosystems that provide habitats for diverse taxa, including spiders. This study examined the effect of agroforestry systems on ground-dwelling spiders across multiple European countries. In each country, several mature agroforestry plots were compared with non-agroforestry agricultural and woody reference plots. Our findings reveal that agroforestry supports species from both open and forested habitats, contributing to landscape-scale biodiversity. Alpha diversity was higher in silvopastures than in forests, but beta diversity (turnover) was not significantly different between agroforestry and other habitat types. Instead, there was a trend towards decreasing spider richness with increasing field size, across all habitat types. High variability in spider diversity across regions suggests that local environmental factors, such as tree species, management practices, and climate, play a key role in shaping spider communities. Our study supports that mosaic of small fields with diverse land uses, combined with seminatural habitats and structurally heterogeneous productive systems like agroforestry, can enhance biodiversity and species-rich agricultural landscapes.

Implementing Brazil’s Forest Code: a vital contribution to securing forests and conserving biodiversity - Rebecca Catherine Brock; Andy Arnell; Will Simonson; Aline C. Soterroni; Aline Mosnier; Fernando Ramos; Alexandre Xavier Ywata de Carvalho; Gilberto Camara; Johannes Pirker; Michael Obersteiner; Valerie Kapos (Biodiversity and Conservation, 2021)
Meeting Brazil’s ambitious national commitments on both climate change mitigation and biodiversity conservation depends on securing its reserves of forest carbon and biodiversity. Brazil’s ‘Forest Code’ is a key tool to reconcile environmental preservation and agricultural production; it limits deforestation and requires forest restoration in illegally deforested areas. However, not all provisions of the law’s 2012 revision have yet been implemented and some are facing new challenges. Using modelled land use change projections for the whole of the country, we show that full implementation and enforcement of the law has the potential to contribute to conserving biodiversity. Biodiversity outcomes will be especially positive if (i) deforested areas are restored in ways that support recolonization by native species and (ii) additional measures are implemented to protect native vegetation in areas like Caatinga dry forests and Cerrado savannas, which may experience added pressure displaced from other regions by Forest Code implementation.